Odpowiedzi

2010-03-19T14:03:34+01:00
A)
(x+y)/3 + y/5 = -2 |*15
(2x-y)/3 - 3x/4 = 1,5 |*12

5(x+y) + 3y = -30
4(2x-y) - 9x = 18

5x + 5y + 3y = -30
8x - 4y - 9x = 18

5x+8y=-30 ------->5*2+8y=-30
-x-4y=18 |*2 10+8y=-30
8y=-40 |*(1/8)
5x+8y=-30 y=-5
-2x-8y=36

3x=6 |*(1/3)
x=2

ODP. x=2 y=-5


b)
(x+1)/(y+2)=5 |*(y+2)
3(2x-5)-4(3y+4)=5

założenie: y+2 różne od 0 więc "y" różne od (-2)

x+1=5(y+2)
6x-15-12y-16=5

x+1=5y+10
6x-12y=36

x=5y+9
6x-12y=36

6(5y+9)-12y=36
30y+54-12y=36
18y=-18
y=-1
x=5y+9 ----------> x=5*(-1)+9
x=-5+9
x=4

ODP. x=4 y=-1